Autoimmune Hepatitis in Brazilian Children: IgE and Genetic Polymorphisms in Associated Genes - Léa Campos de Oliveira; Anna Carla Goldberg; Maria Lucia Carnevale Marin; Karina Rosa Schneidwind; Amanda Farage Frade; Jorge Kalil; Irene Kasue Miura; Renata Pereira Sustovich Pugliese; Vera Lucia Baggio Danesi; Gilda Porta (Journal of Immunology Research)
Pediatric autoimmune hepatitis (AIH) patients present hypergammaglobulinemia, periportal CD8+ cytotoxic T cell infiltration, and cirrhosis. Autoantibody profile defines AIH types 1 and 2 in addition to strong association with HLA-DRB1. We previously detected increased IgE serum levels and sought to compare clinical and histological features according to IgE levels in AIH (n=74, ages 1–14 years) patients. Additionally, we typed 117 patients and 227 controls for functional polymorphisms of IL4, IL13, IL5, and IL4RA genes involved in IgE switching and eosinophil maturation that might contribute to overall genetic susceptibility to AIH. Serum IgE levels were high in 55% of AIH-1, but only in 12% of AIH-2 (P=0.003) patients. Liver IgE was present in 91.3% of AIH-1 patients. The A alleles at both IL13 rs20541 and IL4RA rs1805011 were associated with AIH-1 (P=0.024, OR = 1.55 and P<0.0001, OR = 2.15, resp.). Furthermore, individuals presenting homozygosis for the A allele at IL4RA rs1805011 and HLA-DRB103∗ and/or 13∗ allele had sixfold greater risk to develop the disease (OR = 14.00, P<0.001). The novel association suggests an additional role for IgE-linked immune response genes in the pathogenesis of AIH.